If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Logx(8 + -2x) = 2 (8 * goxL + -2x * goxL) = 2 (8goxL + -2gox2L) = 2 Solving 8goxL + -2gox2L = 2 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -2 + 8goxL + -2gox2L = 2 + -2 Combine like terms: 2 + -2 = 0 -2 + 8goxL + -2gox2L = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-1 + 4goxL + -1gox2L) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-1 + 4goxL + -1gox2L)' equal to zero and attempt to solve: Simplifying -1 + 4goxL + -1gox2L = 0 Solving -1 + 4goxL + -1gox2L = 0 Move all terms containing g to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 4goxL + 1 + -1gox2L = 0 + 1 Reorder the terms: -1 + 1 + 4goxL + -1gox2L = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 4goxL + -1gox2L = 0 + 1 4goxL + -1gox2L = 0 + 1 Combine like terms: 0 + 1 = 1 4goxL + -1gox2L = 1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3p-13=11+9p | | 5z=9z-8 | | 3p-13=11+9 | | (5x-8)2=(5x+12)2 | | -6(x-2)=x+5 | | t*4-2=16 | | 4x^4+2x^2-20x=0 | | X+5*3x-2= | | (3-5x)/(2x-4)=0 | | 2x+3x=15findx | | 18x^2/10y^2*15y^3/24x | | 23-2=x-2+7 | | -2+2w=-4 | | 5(x+5)=7(2x-6) | | x/5-5=15 | | -x+x+5=0 | | (X+5)=7(2x-6) | | 6(3s+6)=54 | | 11m+1=8m+4 | | 6y-2=4y+14 | | 3(x+5)+5+1=31 | | -2(4x-9)=10 | | 12x-4+x=180 | | 9d^2+3d-5=0 | | 8(3m-2)=104 | | 41=6v-7 | | 42y-42y^2=20 | | (2x-1)(x+2)+(3x+1)(x-1)= | | 3(n+4)-8=11-(6-2n)52 | | 3*(2x-1)=9 | | 8x-2y=60 | | 7/(10x)=103/20 |